Treatment Results of Vulvar Intraepithelial Neoplasia in 16 Women - Cüneyt Eftal Taner; İrem Şenyuva; Şevki Göksun Gökulu (Medical Network, 2008)
OBJECTIVE: Clinical outcome after surgical treatment of vulvar intraepithelial neoplasia (VIN). STUDY DESIGN; 16 women with vulvar intraepithelial neoplasia were reviewed. Histologic diagnosis was based on classification of the International Society for the Study of Vulvovaginal Diseases (ISSVD). RESULTS: All cases had unifocal lesions in vulvar examination. In 13 cases (81,5%) lesions were white, in 2 cases (12,5%) lesions were papillary in apprereance and in a case ( 6%) there was an ulcerative lesion. In all cases diameter of the vulvar lesions were less than 2 cm. Local excision was performed for VIN 1 lesions. VIN2 and VIN3 lesions underwent simple vulvectomy. Imiquimod therapy was prefferred for a case with VIN3 lesion who refused surgery. In a case with VIN3 lesion squamous cell carcinoma in situ diagnosed after vulvectomy operation. Recurrence of disease has not yet been diagnosed during the follow up period. CONCLUSION: VIN lesions should be surgically treated and careful long term surveillence is mandatory.